Nickel contamination on MWCNT is related to particle bioactivity but not toxicity in the THP-1 transformed macrophage model. (1st January 2013) - Hamilton, Raymond F.; Girtsman, Teri A.; Xiang, Chengcheng; Wu, Nianqiang; Holian, Andrij
The potential pathogenic effects from exposure to various MWCNT have not been adequately determined. One potential contributing factor to MWCNT bioactivity could be metal contamination that occurs during production. This study examined the toxicity and bioactivity (NLRP3 inflammasome activation), of 24 commercially available MWCNT in a macrophage-like differentiated THP-1 cell line. Inflammasome activation, via IL-1β release, was highly correlated to Ni content. Soluble NiCl2 and insoluble Ni nanopowder were tested in the same model at varying concentrations with no inflammasome activation. Ni-decorated MWCNT were also tested in the THP-1 model and the results also correlated with Ni content. These results demonstrated that Ni content correlated to NLRP3 inflammasome activation, but not toxicity. Taken together, the results suggest that Ni, when fixed to MWCNT, is highly bioactive and potentially proinflammatory. The related mechanism probably involves lysosomal rupture, release of cathepsin B, and NLRP3 activation.